Fast electrical spatial light modulation in quantum confined Stark heterostructure metasurfaces - Xu, Jiayang (Nanyang Technological University, 2024)
Semiconductor-based tunable metasurfaces offer a versatile solution for dynamic light control, attracting significant research interest. However, current designs face the challenge of limited modulation speeds, typically in the MHz range. Here, we propose a multiple-quantum-well-based mid-infrared tunable metasurface with Mie resonance, realizing an experimental modulation speed of approximately 1 GHz. Electrical tuning is accomplished by quantum-confined Stark effect, utilizing electron resonant tunneling between two coupled quantum wells which is adjustable by voltage. This performance holds potential for high-speed optical communication, dynamic beam shaping, as well as advanced photonic devices.